Isoflavone and Protein Constituents of Lactic Acid-Fermented Soy Milk Combine to Prevent Dyslipidemia in Rats Fed a High Cholesterol Diet - Kobayashi, Maki (Nutrients, 2014)
A high cholesterol diet induces dyslipidemia. This study investigated whether isoflavone aglycones in lactic acid-fermented soy milk (LFS) improve lipid metabolism in rats fed a high cholesterol diet. Male Sprague-Dawley rats aged seven weeks were fed an AIN-93G diet, a 1% cholesterol diet (a high cholesterol diet), a high-cholesterol diet containing 4% isoflavone extract of LFS (LFS extract diet), a high-cholesterol diet containing 19.4% ethanol-washed LFS (ethanol-washed LFS diet, isoflavone-poor diet), or a high cholesterol diet containing 23.2% intact LFS (intact LFS diet) for five weeks. The plasma total cholesterol (TC) level was increased in the rats fed the LFS extract diet compared with those fed the high cholesterol diet. The TC level was decreased by the intact LFS and ethanol-washed LFS diets. The cholesterol-lowering effect was stronger in the rats fed the intact LFS diet than those fed the ethanol-washed LFS diet. The plasma triglyceride (TG) level was unchanged in the rats fed the LFS extract diet, but it decreased in rats fed the intact LFS and ethanol-washed LFS diets. Although, compared with the high cholesterol diet, the LFS extract and ethanol-washed LFS diets did not reduce hepatic cholesterol and TG, both levels were remarkably lowered by the intact LFS diet. These results suggest that the improvement in lipid metabolism of rats fed a high-cholesterol diet containing LFS isoflavone aglycones is not due to an independent effect but due to a cooperative effect with soy protein.